Love of Money and Unethical Behavior Intention: Does an Authentic Supervisor’s Personal Integrity and Character (ASPIRE) Make a Difference? - Tang, Thomas Li-Ping; Liu, Hsi (2012)
We investigate the extent to which perceptions of the authenticity of supervisor’s personal integrity and character (ASPIRE) moderate the relationship between people’s love of money (LOM) and propensity to engage in unethical behavior (PUB) among 266 part-time employees who were also business students in a five-wave panel study. We found that a high level of ASPIRE perceptions was related to high love-of-money orientation, high self-esteem, but low unethical behavior intention (PUB). Unethical behavior intention (PUB) was significantly correlated with their high Machiavellianism, low self-esteem, and low intrinsic religiosity. Our counterintuitive results revealed that the main effect of LOM on PUB was not significant, but the main effect of ASPIRE on PUB was significant. Further, the significant interaction effect between LOM and ASPIRE on unethical behavior intention provided profoundly interesting findings: High LOM was related to high unethical behavior intention for people with low ASPIRE, but was related to low unethical intention for those with high ASPIRE. People with high LOM and low ASPIRE had the highest unethical behavior intention; whereas those with high LOM and high ASPIRE had the lowest. We discuss results in light of individual differences, ethical environment, and perceived demand characteristics.
Keywords: measurement invariance; panel study; Demographic; Moderator; Perceived demand characteristics; Counterproductive; Work deviance; Unethical behavior intention; Spiritual; Justice; Fairness; Trustworthy leader; Transparent help; Caring servant; Honesty and integrity; Authentic supervisor’s personal integrity and character; Love/stewardship of money; Money ethics; Meaning of money